Study guides

☆☆

Q: To solve the system given below using substitution it is best to start by solving the second equation for y?

Write your answer...

Submit

Related questions

The first step is to solve one of the equations for one of the variables. This is then substituted into the other equation or equations.

You use substitution when you can solve for one variable in terms of the others. By substituting, you remove one variable from the equation, which can then be solved. Once you solve for one variable, you can use substitution to find the other.

If you mean x+2y = -2 and 3x+4y = 6 then by solving the simultaneous equations by substitution x = 10 and y = -6

By elimination and substitution

The first step is to show the equations which have not been shown.

The first step is usually to solve one of the equations for one of the variables.Once you have done this, you can replace the right side of this equation for the variable, in one of the other equations.

Isolating a variable in one of the equations.

You'd need another equation to sub in

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

Substitution method: from first equation y = 5x - 8. In the second equation this gives 25x - 5(5x - 8) = 32 ie 25x - 25x + 40 = 32 ie 40 = 32 which is not possible, so the system has no solution. Multiplication method: first equation times 5 gives 25x - 5y = 40, but second equation gives 32 as the value of the identical expression. No solution.

Substitute the values for the two variables in the second equation. If the resulting equation is true then the point satisfies the second equation and if not, it does not.

You are trying to find a set of values such that, if those values are substituted for the variables, every equation in the system is true.

I'll assume the simplified case of two equations, with two variables each. Some of the methods can be extended to more complicated cases.Substitution: Solve for one variable in one equation, replace it in the other equation.Setting two quantities equal: For example, if 5x + 3y = 10, and 5x - 2y = 0, solve each equation for "5x", and set the two equal, with the result: 10 - 3y = 2y.Addition/subtraction: Add or subtract one equation (or a multiple of one equation) to the other. In the previous example, if you subtract the second equation from the first, you get an equation that doesn't contain x.In any of these cases, after solving for a single variable, replace in one of the original equations to get the other variable.

Without a second independent equation, it's not a 'system' yet.

If the process of substituting leads to an identity rather than an equation then the system has infinitely many solutions.

Without a second independent equation, it's not a 'system' yet.

Without a second independent equation, it's not a 'system' yet.

The main advantage is that many situations cannot be adequately modelled by a system of linear equations. The disadvantage is that the system can often get very difficult to solve.

u can use gauss jorden or gauss elimination method for solving linear equation u also use simple subtraction method for small linear equation also.. after that also there are many methods are available but above are most used

If you mean: x = 8y+5 and 3x-2y = 11 then the simultaneous equations can be solved by a process of elimination. -------------------- Since the first equation is solved for x, substitution should be easy. There is no "right" answer to this question - it depends on your taste and experience.

Substitution is a way to solve without graphing, and sometimes there are equations that are impossible or very difficult to graph that are easier to just substitute. Mostly though, it is a way to solve if you have no calculator or cannot use one (for a test or worksheet).

Newton's Second Law: F=ma. Solving for a: a = F/m.

You do the following: 1) Solve one of the equations for one of the variables 2) Substitute this variable in the other equation or equations 3) Simplify This should normally give you one less equation than the original set, with one less variables. For example:

From first equation: y = 2x - 5Substitute this in second equation: 3(2x - 5) - x = 5, ie 6x - 15 - x = 5ie 5x = 5 + 15 so x = 4 and y = 3

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

People also asked